2015
DOI: 10.1111/1750-3841.12775
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Assessment of Beef Tenderloin Steaks from Various USDA Quality Grades at 3 Degrees of Doneness

Abstract: A consumer study was conducted to determine palatability ratings of beef tenderloin steaks from USDA Choice, USDA Select, and USDA Select with marbling scores from Slight 50 to 100 (USDA High Select) cooked to various degrees of doneness. Steaks were randomly assigned to 1 of 3 degree of doneness categories: very-rare, medium-rare, or well-done. Consumers (N = 315) were screened for preference of degree of doneness and fed 4 samples of their preferred doneness (a warm-up and one from each USDA quality grade tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Eating quality of beef is determined by juiciness, tenderness and flavor [ 23 ]. Marbling, or intramuscular fat deposition, is highly related to meat quality and a positive eating experience [ 24 , 25 ]. In the United States, the primary system used for beef evaluation is the United States Department of Agriculture beef grading system, and amount of marbling is one of the major factor in determining the official quality grade of young beef carcasses (Prime, Choice, Select, Standard).…”
Section: Discussionmentioning
confidence: 99%
“…Eating quality of beef is determined by juiciness, tenderness and flavor [ 23 ]. Marbling, or intramuscular fat deposition, is highly related to meat quality and a positive eating experience [ 24 , 25 ]. In the United States, the primary system used for beef evaluation is the United States Department of Agriculture beef grading system, and amount of marbling is one of the major factor in determining the official quality grade of young beef carcasses (Prime, Choice, Select, Standard).…”
Section: Discussionmentioning
confidence: 99%
“…with increased DOD (Parrish et al, 1973;Lorenzen et al, 2005;O'Quinn et al, 2015). However, a large percentage of beef consumers prefer steaks to be cooked to at least a medium DOD (Cox et al, 1997;Reicks et al, 2011).…”
mentioning
confidence: 99%
“…In a similar study, overall liking ratings of top sirloin steaks declined as the degree of doneness increased toward well done (Savell and others ). O'Quinn and others () reported that tenderness and juiciness liking ratings decreased as degree of doneness increased. Overall, all 3 populations selected grilling and medium/medium well as the more preferred cooking method and degree of doneness, respectively (Table ).…”
Section: Resultsmentioning
confidence: 96%